2019
DOI: 10.1001/jamainternmed.2018.5086
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physician Variation in Provision of Low-Value Services

Abstract: Importance: Facing new financial incentives to reduce unnecessary spending, provider organizations may attempt to reduce wasteful care by influencing physician practices or selecting more cost-effective physicians. However, physicians’ role in determining the use of low-value services has not been well described. Objective: To quantify variation in provision of low-value health care services among primary care physicians and to estimate the proportion of variation attributable to physician characteristics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 41 publications
4
77
1
Order By: Relevance
“…This strategy differs from prior approaches broadly assessing low-value care among Medicare beneficiaries, which depict low-value care as counts among 100 beneficiaries, making direct comparisons between VA and Medicare beneficiaries challenging. 5 , 7 , 8 Nevertheless, these data, in concert with the growing body of literature on this topic, suggest that low-value care is common and occurs across multiple disease states in the VHA, as it does among Medicare and private insurance beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy differs from prior approaches broadly assessing low-value care among Medicare beneficiaries, which depict low-value care as counts among 100 beneficiaries, making direct comparisons between VA and Medicare beneficiaries challenging. 5 , 7 , 8 Nevertheless, these data, in concert with the growing body of literature on this topic, suggest that low-value care is common and occurs across multiple disease states in the VHA, as it does among Medicare and private insurance beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…Use of low-value care is especially prevalent among older adults in the US. 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 A 2014 study 2 found that among 26 low-value services in 6 categories (ie, cancer screening, diagnostic and preventive testing, preoperative testing, imaging, cardiovascular testing and procedures, and other surgical procedures), 24% to 41% of individuals enrolled in traditional fee-for-service Medicare (TM) received at least 1 low-value service in 2009. The rate of use of low-value care varied across services, ranging from 0.1% for electroencephalography for headache to 12.4% for imaging for low-risk low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…While accountability may have driven care to lower cost settings and reduced waste, we found relatively high unit cost growth in most care services. Although limited by its reliance on administrative data, and an inability to adjust for changing patient needs, these initial findings invite further research examining the effectiveness of efforts to reduce components of per capita Medicare inflation by reducing low-value care provision (reducing service use), 5 reducing estimated unit costs for longitudinal services (reducing episode costs), or enhancing provider productivity (improving care efficiency). 6 Figure 1 For Medicare fee-for-service enrollees younger than age 65 (top) and 65 years old and older (bottom), compound annual inflation rates for the period 2007-2017 overall for each service (in the black circle) and for each inflation rate component (the proportion of the service population that used the service, the number of events per service, the estimated cost per event (for single-use services), and the number of days per episode and the estimated cost of each episode day (for longitudinal services).…”
Section: Discussionmentioning
confidence: 99%